CLASSIFICATION OF JC VIRUS SEROSTATUS DEPENDS UPON ASSAY SELECTION: A COMPARISON OF BIOGEN AND HPA ASSAYS. (29th November 2012) - Raffel, J; Hunt, D; Topping, J; Bremner, J; Giovannoni, G
Abstract : Introduction: JC virus (JCV) seroposivity is a risk factor for the future development of progressive multifocal leukoencephalopathy in people with multiple sclerosis (MS) about to start natalizumab. In the UK, two main assays are commonly available for the detection of JCV antibodies: the 2-step STRATIFY JCV assay, designed and validated by Biogen Idec, and the haemagglutination inhibition (HI) assay, provided by the Health Protection Agency (HPA), Colindale. However, the level of correlation between these two assays is not yet known. Methods: One hundred samples from 73 patients were tested using both assays, for comparison of serostatus classification. Results: Sera with STRATIFY JCV first-step 'seropositive' or 'seronegative' antibody titres showed good inter-assay agreement of serostatus (n=80, κ coefficient=0.91), whereas those with STRATIFY JCV first-step 'indeterminate' antibody titres showed poor inter-assay agreement (n=20; kappa coefficient=0). Surprisingly, all 20 sera with 'indeterminate' first step STRATIFY JCV antibody titres were classified as seropositive after the second 'inhibition' step of the assay (ie, all showed >40% inhibition), in contrast with previous published data published Biogen data where only 62% of sera showed >40% inhibition. Conclusions: These results may reflect a lack of sensitivity of the HPA assay or a lowered cut-off adopted by the STRATIFY JCV assay. Independent blinded assessment of multiple assays, using sera from patients with positive urinary JCV DNA, or natalizumab-associated PML cases, would help clarify this issue.